2020
DOI: 10.1186/s12872-020-01707-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Inflammatory Index with cardiovascular disease in Kurdish adults: results of a prospective study on Ravansar non-communicable diseases

Abstract: Background Various diets and dietary compounds, through their inflammatory properties, are involved in the pathogenesis of chronic diseases including Cardiovascular Diseases (CVDs). Dietary Inflammatory Index (DII) can evaluate the inflammatory properties of diet. The purpose of this study was to determine the association between DII and CVDs in participants of the Ravansar Non-Communicable Diseases (RaNCD) cohort study, Kermanshah, Iran. Materials The present cross-sectional study was conducted using the re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Additionally, previous papers have shown an inverse association between dietary antioxidants and the risk of CVDs and metabolic syndrome (MetS) [ 7 , 14 ]. On the other hand, scientific evidence has shown that an inflammatory diet is correlated with an increased risk of developing type 2 diabetes, hypertension, cardiovascular diseases (CVDs), and non-alcoholic fatty liver (NAFLD) [ 15 17 ]. According to a review study, antioxidants have anti-inflammatory effects although different types of antioxidants may have different effects since they are structurally and chemically different [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous papers have shown an inverse association between dietary antioxidants and the risk of CVDs and metabolic syndrome (MetS) [ 7 , 14 ]. On the other hand, scientific evidence has shown that an inflammatory diet is correlated with an increased risk of developing type 2 diabetes, hypertension, cardiovascular diseases (CVDs), and non-alcoholic fatty liver (NAFLD) [ 15 17 ]. According to a review study, antioxidants have anti-inflammatory effects although different types of antioxidants may have different effects since they are structurally and chemically different [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have primarily centered on exploring the link between DII and CVD. In the Ravansar Non-Communicable Disease (RaNCD) cohort study 16 , where 9% of participants had prior CVD records, the investigation set out to scrutinize the connection between DII and CVD risk. The findings unveiled that higher adherence to a pro-inflammatory diet correlated with an elevated risk of CVD ( OR : 1.4, 95% CI : 1.1–1.8).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a greater intake of animal fats and sodium is associated with the onset of micro albuminuria, while a greater intake of carotenoids, which have an anti-inflammatory effect, is associated with an increase in GFR ( 32 ). One of the potential mechanisms adding to the relationship between DII and the risk of renal disease is the impact of diet-related chronic inflammation in the upregulation of various pro-inflammatory mediators like TGF-β, TNF-α, IL-6, and CRP ( 14 ). In contrast, others have shown that the DII score is unrelated to serum hs-CRP and biomarkers of kidney function in elderly patients ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding the role of inflammation in CKD in relation to diet can foster the development of effective prophylactic and therapeutic strategies against the underlying inflammation in CKD patients. While the inflammatory pathophysiology may not be similar in patients with chronic renal failure, persistent low-grade inflammation has been hypothesized as a risk factor for CKD ( 14 ). Dietary intake may contribute to the development of an inflammatory condition and trigger the risk of CKD ( 5 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%